Whole genome sequencing resource identifies 18 new candidate genes for autism spectrum disorder - C Yuen, Ryan K; Merico, Daniele; Bookman, Matt; L Howe, Jennifer; Thiruvahindrapuram, Bhooma; Patel, Rohan V; Whitney, Joe; Deflaux, Nicole; Bingham, Jonathan; Wang, Zhuozhi; Pellecchia, Giovanna; Buchanan, Janet A; et al. (Nature neuroscience, 2017)
Yuen et al . developed a cloud-based database with 5,205 whole genomes from families with autism spectrum disorder (ASD). They identified 18 new candidate ASD-risk genes and approximately 100 risk genes and copy-number loci, which account for 11% of the cases. They also found that individuals bearing mutations in ASD-risk genes had lower adaptive ability. We are performing whole-genome sequencing of families with autism spectrum disorder (ASD) to build a resource (MSSNG) for subcategorizing the phenotypes and underlying genetic factors involved. Here we report sequencing of 5,205 samples from families with ASD, accompanied by clinical information, creating a database accessible on a cloud platform and through a controlled-access internet portal. We found an average of 73.8 de novo single nucleotide variants and 12.6 de novo insertions and deletions or copy number variations per ASD subject. We identified 18 new candidate ASD-risk genes and found that participants bearing mutations in susceptibility genes had significantly lower adaptive ability ( P = 6 × 10 −4 ). In 294 of 2,620 (11.2%) of ASD cases, a molecular basis could be determined and 7.2% of these carried copy number variations and/or chromosomal abnormalities, emphasizing the importance of detecting all forms of genetic variation as diagnostic and therapeutic targets in ASD.